Religion, conflict, and democracy in modern Africa : the role of civil society in political engagement - Elolia, Samuel K.; Adogame, Afeosemime U. (Afeosemime Unuose), 1964- (Eugene, Or. : Pickwick Publications, 2012)
Spanning various regions of Sub-Saharan Africa, the authors of this volume come together to explore the complex relationship between religion and democracy in contemporary Africa. As a result of the end of the Cold War and the fall of the Soviet Union, many African countries have come to the realization, however partial, that political and social change is inevitable in spite of government heavy-handedness and threats. It has also become evident that no political system that refuses to permit freedom of political expression and alternative systems of governance could continue to be sustained. It is in precisely this political climate that religious institutions have collaborated with other elements of civil society to call for political reforms, with the church often becoming the prominent voice against oppressive governments in countries such as Kenya and South Africa. It is the purpose of this book to assess how religion shapes political issues and to what extent religious forces influence the civil society. By acknowledging the role of the civil society, the essays recognize the resilience that comes out of Africa even when the sociopolitical situation seems unbearable.
pt. 1. The theoretical perspectives of religion in Africa. Violence and social imagination : rethinking religion and politics in Africa / Emmanuel M. Katongole -- The African renaissance and religion / Elias K. Bongmba -- Religion, violence, and conflict : Ujamaa-therapy as a dynamic response to ethnic particularities in Africa / Cyril Orji -- pt. 2. Religion, democracy, and conflict resolution in East Africa. Religion and the road to democracy in Kenya / Samuel K. Elolia -- Forgiveness : the divine gift of peace, reconciliation, and healing / Adam K. arap Chepkwony -- Church and state conflicts in Uganda : President Idi Amin kills the Anglican archbishop / Emmanuel Kalenzi Twesigye -- pt. 3. Religion and state formation in the shadow of apartheid in South Africa. From apartheid's Christian hegemony to religious pluralism / Samuel Paul -- Instruments or inhibitors of civil society? : the role of Christians in the formation of public policy / James R. Cochrane -- Bahia and Zion : the eruption of new religions of the poor, political implications of Afro-Brazilian and South African independent churches / Iain S. Maclean -- pt. 4. Religious pluralism and social change in West Africa. Religion and social change in multi-ethnic Nigerian society / Ukachukwu Chris Manus, Bolaji Olukemi Bateye -- Shari'a, democracy, and civil society : the case of northern Nigeria / Umar Habila Dadem Danfulani -- Nigerian civil government and the application of Islamic law : can conflict lead to accommodation? / Yushau Sodiq.
Includes bibliographical references.
Keywords: Religion and politics -- Africa; Christianity and politics -- Africa; Democracy -- Africa; Church and state -- Africa